An Analysis on Halal Tourism Potential: An Overview of the Educational Aspects and Number of Tourist Visits - Martaleni, Martaleni; Hermawati, Adya; Handhajani, Sri Budhi Pudji; Yasa, Ni Nyoman Kerti (Graduate School, Universitas Brawijaya, 2021)
The phenomenon of the Islamic economy recently is a principal part of the global economy. The brands and services with halal/sharia concept in many products have become increasingly trending in the global economy, including in the tourism industry. Opportunities for the development of halal tourism are widely open as the rapidly growing Muslim population in the world. This study aims to analyse the potential of halal tourism from the educational aspect and the number of tourist visits to Bromo Tengger National Park. Primary data were collected through distributing questionnaires to Muslim tourists, in which the judgment sampling method was used for the selection of respondents. The number of respondents who filled out the questionnaire was 250 people. Furthermore, the data were analyzed using the exploratory multivariate method. Tourist education and the number of tourist visits to Bromo Tengger act as aspects that can influence tourist perceptions in providing an assessment of the potential of halal tourist destinations. The results showed that the tourists gave a pretty good perception for every aspect of measuring halal tourist destination. Based on the research results, it can be concluded that the Bromo Tengger destination has the potential as a halal tourist destination. Keywords: halal tourism, potential, tourists.